2020
DOI: 10.3389/fmicb.2020.02010
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Flow in Diazotrophic Cyanobacterium Aphanizomenon flos-aquae Is Altered by Cyanophage Infection

Abstract: Viruses can significantly influence cyanobacteria population dynamics and activity, and through this the biogeochemical cycling of major nutrients. However, surprisingly little attention has been given to understand how viral infections alter the ability of diazotrophic cyanobacteria for atmospheric nitrogen fixation and its release to the environment. This study addressed the importance of cyanophages for net 15 N 2 assimilation rate, expression of nitrogenase reductase gene (nifH) and changes in nitrogen enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…We found that the effect of cyanophages on carbon and nitrogen cycling and cellular metabolism was significant yet varied widely depending on the stage of the infection process (e.g., cyanophage adsorption vs. DNA replication vs. release), and the state of the host culture (culture undergoing infection/lysis vs. recovering culture). Our observations suggest that cyanobacteria underwent a physiological state shift towards lower efficiency carbon and energy cycling, as well as to the reduced nitrogen transport from heterocytes (N-fixing cells) to vegetative cells [6,7]. The lysis of cyanobacterial cells was associated with a release of ammonium and other compounds that promoted changes in co-occurring microbes.…”
mentioning
confidence: 78%
“…We found that the effect of cyanophages on carbon and nitrogen cycling and cellular metabolism was significant yet varied widely depending on the stage of the infection process (e.g., cyanophage adsorption vs. DNA replication vs. release), and the state of the host culture (culture undergoing infection/lysis vs. recovering culture). Our observations suggest that cyanobacteria underwent a physiological state shift towards lower efficiency carbon and energy cycling, as well as to the reduced nitrogen transport from heterocytes (N-fixing cells) to vegetative cells [6,7]. The lysis of cyanobacterial cells was associated with a release of ammonium and other compounds that promoted changes in co-occurring microbes.…”
mentioning
confidence: 78%
“…Previous studies found two cyanophages, Vb-AphaSCL131 and Vb-AphaM-CL132, belonging to Siphoviridae and Myoviridae , respectively, in the purified lysates of Aphanizomenon flos-aquae ( Gelzinis et al, 2015 ; Sulcius et al, 2019 ). After cell lysis by Vb-AphaSCL131, substantial release of ammonium into the culture medium was detected ( Kuznecova et al, 2020 ). Although the growth of Aphanizomenon flos-aquae was significantly inhibited by Vb-AphaSCL131 infection, nifH gene expression level and the nitrogen fixation rates are barely altered, as cyanophage replication and progeny production within vegetative cells does not interfere with the N 2 fixation process in heterocysts.…”
Section: Viral Shunt Promotes Marine Nitrogen Flow Along With Microbi...mentioning
confidence: 99%
“…Although the growth of Aphanizomenon flos-aquae was significantly inhibited by Vb-AphaSCL131 infection, nifH gene expression level and the nitrogen fixation rates are barely altered, as cyanophage replication and progeny production within vegetative cells does not interfere with the N 2 fixation process in heterocysts. Intriguingly, Vb-AphaSCL131 can also reduce the transport of fixed nitrogen from heterocysts to vegetative cells, which leads to nitrogen accumulation at the poles of heterocysts ( Kuznecova et al, 2020 ).…”
Section: Viral Shunt Promotes Marine Nitrogen Flow Along With Microbi...mentioning
confidence: 99%
“…For instance, the source of N for cyanophage protein synthesis has been shown to shift over the course of infection from mostly host derived in the early stages to more environmentally derived later on (Waldbauer et al 2019), which suggests that the nutrient content of phytoplankton hosts at the start of an infection may not always suit the pathogen to reproduce optimally. Some viruses infecting phytoplankton have strategies to cope with nutrient limitation within their host, for example, by minimizing interference with N‐fixation (Kuznecova et al 2020) or manipulation of host metabolism to boost N or P uptake (Monier et al 2012, 2017). These strategies can result in a reduced carbon:nutrient content of infected versus healthy host tissue (Ankrah et al 2014), stimulating viral reproduction, but also enriching the quality of the cell material released in the water after cell lysis (Ankrah et al 2014, Zheng et al 2020).…”
Section: Other Factors Masking Stoichiometrically Driven Trendsmentioning
confidence: 99%